STUDY OF TURBULENCE PHENOMENON BASED ON WRFARW MODEL SIMULATION WITH HYBRID MASS COORDINATE (CASE STUDY: BATIK AIRLINES FLIGHT DATE OCTOBER 24, 2017) - Alfi Al Halimy, Nabila
The report from the National Safety and Transportation Commission (NTSC) stated that there were convective clouds around the turbulence area experienced by Batik Airlines on October 24, 2017. However, it is not known whether the turbulence was generated by convective clouds or other factors. The data used in this study are NCEP-FNL data, report data from the KNKT, sounding data, and Himawari-8 Satellite data. This research consists of several stages. The first stage is to simulate the WRF-ARW model by modifying the vertical grid density. Then the results of the model are verified so that the simulation that is closest to the observation is obtained. The simulation is used as a control run in the next stage. Then, identification of the effect of convective activity was carried out with 3 types of experiments, namely CTRL (control run), NOMP (non-microphysics parameterization), and NOLH (non-latent heating). The results showed that simulation 4 with an eta level configuration of 82 and a density below had an EDR value of 0.22 m2/3 s-1 with a moderate turbulence category. Turbulence in simulation 4 is more obvious than in other simulations based on the verification results. The phenomenon of turbulence experienced by Batik Airlines aircraft on October 24,2017 was NCT. The condition of the atmosphere is unstable so that it is not possible for the mountain wave phenomenon to occur. The cause of turbulence is dominated by buoyancy which is larger than wind shear. The Ri value indicates the area has the potential to become turbulent with an EDR intensity of 0.22 m2/3 s-1 in the moderate turbulence category.